Central Bank Digital Currency : A Payments Perspective - World Bank (World Bank, Washington, DC, 2021)
Payment and settlement systems and services have become vital components of the economic life of contemporary societies. Over the last decades, they have gone through several waves of reforms that have changed the landscape of the national payments system (NPS) in virtually every country in the world. Recently, the issuance of central bank digital currency (CBDC) has become a highly debated financial-sector topic worldwide. The international financial community is studying aspects of CBDC, from design to implementation, and implications for the financial system, including on policy, regulation, and oversight and the economy more broadly. This guidance note is intended to be used primarily by central banks and relevant public authorities considering the issuance of CBDC and by those institutions and individuals supporting them in this process.